HIV and lung cancer: a single cancer center experience - Palecki, Julia; Tucker, Matthew; Bernstein, Andrew; Melby, Garrett; Zhan, Tingting; Micaily, Ida (Frontiers in Oncology, 2025)
Lung cancer (LC) is the leading cause of cancer death in people living with HIV (PLWH) and disproportionately affects this group regardless of CD4 count. At the Sidney Kimmel Comprehensive Cancer Center (SKCCC) at Jefferson Health, we treat an underserved PLWH population with LC and aim to study their clinical course, as they are often excluded from LC trials. We retrospectively reviewed 36 PLWH diagnosed with LC at Jefferson Health from 2016 to 2023. We found that 24 patients were male, 20 patients were Black, and that the median age of LC diagnosis is 66 years (range 38-83 years). 27 patients had non-small cell lung cancer (NSCLC) (20 adenocarcinoma, 7 squamous), 3 had small cell lung cancer (SCLC). 24 patients had undetectable viral loads, and 35 patients were on antiviral therapy. Advanced-stage disease was seen in 32 patients, with a 1.3-year OS (95% CI: 0.8-3.8 years). Of 18 patients with molecular testing available, 4 had KRAS mutations, and 1 had targetable EGFR mutations. Of 16 tested for PD-L1, 8 patients had 1-49% expression, and 1 patient had >50%. Our cohort showed more advanced disease at presentation, younger age at diagnosis, and poor OS despite most patients having undetectable HIV viral loads on antiviral therapy, suggesting a link between well-controlled HIV and aggressive LC that warrants further study.